Microlearning-Oriented Explainer Videos (MOEV) to Improve Students' Digital Skills in Developing Print Media for Early Childhood - Yafie, Evania; Samah, Norazrena Abu; Kustiawan, Usep; Sutama, I Wayan; Iriyanto, Tomas (Tarbawi : Jurnal Ilmu Pendidikan, 2025)
This research was conducted to produce Microlearning-Oriented Explainer Videos (MOEV) as a learning resource for the development of students' digital competence through early childhood print media. In this study, a Research and Development (R&D) design is used in the development paradigm of ADDIE, which stands for Analysis, Design, Development, Implementation, and Evaluation. The data analysis method used was descriptive percentage analysis. The results of the expert validity test indicated that MOEV was eligible for use as the average validation score achieved by media experts was 97%, material experts was 91%, and learning design experts was 93%. Results of the practicality test showed that the practicality reached a score of 92%. The results show that MOEV is a tremendous and innovative interactive learning medium that students can explore independently to understand in depth using visual and audio materials. Further empirical validation of this research is needed to determine the long-term viability and potential scalability of MOEV to other courses.